Muscle imbalance among elite athletes. Issue 4 (27th March 2011) - Franettovich, M; Hides, J; Mendis, M D; Littleworth, H
Abstract : Background: Previous research in team sports, such as football and cricket, has found muscle imbalances in the lumbo-pelvic region, especially in muscles involved in joint stability and protection. It is thought that these muscle imbalances occur as a result of the specific requirements of the sport. However, this pattern of muscular imbalance may not be isolated to team sports and may potentially exist in elite athletes performing Olympic sports. Objective: To investigate similarities in patterns of muscle imbalance among elite athletes performing team and individual sports. Design: Comparative case studies. Setting: MRI examinations were carried out in a hospital setting. Participants: Elite athletes participating in a range of team and individual sports including cycling, heptathlon, marathon and skeleton racing. Main outcome measurements: Muscle cross-sectional areas (CSA) of individual muscles of the trunk and pelvic region. Results: CSA of the trunk muscles show variation across muscle groups but evidence of imbalance within these groups. Conclusion: Muscle imbalances exist in a wide range of athletes performing at the elite level and may be related to injury occurrence. Identification of the pattern of imbalance for different sports will enable muscle specific rehabilitation.